Transtornos do espectro do autismo no âmbito das Políticas Públicas de Saúde. - Albuquerque, Nayana Mara Arruda (2023)
Autism has been a subject at the heart of relevant discussions, both with regard to the national sphere and with regard to the international parameter. Several agents, such as: autistic people themselves, professionals, academics, managers and other activists, have fostered vast debates based on different conceptions regarding the probable etiological factors, the supposedly and hypothetically effective treatment methodologies, the nosographic description of the disorder , as well as the forms of organization of care policies and the general legal framework regarding the guarantee of rights. However, despite the numerous contributions to the understanding not only of autism, but of other psychopathologies, Psychoanalysis, in certain situations, is pushed aside by a pseudoscientific discourse, in which nosological psychiatry and the neurosciences prevail with a certain absolutism. Aiming to explore and analyze official documents as well as regulations and regulations of the Ministry of Health (MS) concerning technologies and care tools, resources and therapeutic attributes as well as analyzes and diagnoses offered in the Unified Health System (SUS) Network to people with Autism Spectrum Disorder (ASD), the objective was also to identify the perspective within this context of an articulated connection with the Family Health Strategy (ESF) and to analyze some concepts and methods of approaches to the work (“treatment”) of people with ASD in the context of Public Health. The methodology will be based on the following categories of analysis: presentation, conceptions about autism, diagnostic guidelines, general guidelines for care and the organization of the care network. These categories were defined because they are correlated with the main axes through which both documents address the different aspects related to the theme. Still on the study methodology, we used Bibliographic and Documentary Research with a qualitative approach. For data analysis and weighting purposes, this research consisted of reflection and weighting with regard to the conditions and states of production as well as the assimilation of the meaning of contents developed in the most diverse contexts and circumstances with regard to individuals with Disorder Autism Spectrum. Thus, carrying out this research was an opportunity to enter the field of study and put into practice the theoretical knowledge acquired, as well as to realize that the discussion about the theme of autism culminates in a much broader discussion about the social policies related to this population and it was observed that people with ASD need to be respected in their particularities and singularities.